(3QSGdI aj ChbGa GdbQBfs - (3eLghds
(3ChdgG (B:s
(3GYde Cf aj LejY GdbQBf NeSI BdGa hKeGfI hYTQhf hbaG efgG YTQI ehGVY JSei hba ZaQGf bGd Udi Gddg Ydjg hSde (B: " (3ef Vef dj Cf jba Ydi YTQI ehGVY ef GdbQBf VefJ dg GdLfI (B"s
(3BNQgG (B:s
(3YHS(B: (3aef TGA PcQg, GdZGTjI (B: (3ajgG Yjf LGQjI , ShQI GdHdO (B: (3Cf df jbOQ Ydjg CMO , GdTeS (B: (3ef OSgGs
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
Keywords: (3GdbQGAGJ hGdJLhjOs